РАЗВИТИЕ ПРЕДСТАВЛЕНИЙ О ФУНДАМЕНТАЛЬНЫХ ПРИНЦИПАХ ВОЗНИКНОВЕНИЯ ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА. СИСТЕМНЫЙ АНАЛИЗ РЕГУЛЯЦИИ ДЕЯТЕЛЬНОСТИ СЕРДЦА В НОРМЕ - В. С. Хазов (Архивъ внутренней медицины, 2012)
The modern generally accepted occlusive coronarogenic theory of heart disease (CHD) doesn’t satisfy the needs of either science or the public at large. Against the background of critically accumulated data that cannot be explained by this theory, the mortality and death rate caused by different forms of CHD have been growing. Such claims to the dominating concept prove to make one doubt not only the correctness of the concepts related to the essence of CHD but also the adequacy of the basic theoretical directions that laid the foundation of the theory in the last century. The paper both criticizes some outdated basic notions and presents the new concept of CHD based on the method of system analysis in the form of the theory of functional system with all the ensuing consequences.